2013
DOI: 10.1007/s12639-013-0326-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of canine trypanosomiasis in certain areas of Andhra Pradesh

Abstract: A total of 937 dogs were screened for Trypanosoma evansi infection by wet blood film, blood smear staining techniques and micro haematocrit centrifugation technique (MHCT). In the present study, 2.28 % of male dogs and 2.40 % of female dogs were found positive by MHCT method. The findings indicated that there was no effect of T. evansi infection on sex of dogs. Higher prevalence of T. evansi infection was observed in Mongrel than in Pomeranian, Cross breeds, German Shepherd, Doberman and Labrador breeds. Age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…However, dogs can also get the infection by ingestion of fresh animal carcasses that died recently from trypanosomiasis and through oral experimental infection (Nwoha, 2013). Higher prevalence of T. evansi infection was observed in Mongrel than in Pomeranian, Cross breeds, German Shepherd, Doberman and Labrador breeds in Andhra Pradesh (Prasad et al, 2015). The clinical signs in the present study is in accordance with Behera et al (2018) and Saurabh Kumar (2010), who also reported corneal opacity, high temperature and lymphnode enlargement.…”
Section: Resultssupporting
confidence: 89%
“…However, dogs can also get the infection by ingestion of fresh animal carcasses that died recently from trypanosomiasis and through oral experimental infection (Nwoha, 2013). Higher prevalence of T. evansi infection was observed in Mongrel than in Pomeranian, Cross breeds, German Shepherd, Doberman and Labrador breeds in Andhra Pradesh (Prasad et al, 2015). The clinical signs in the present study is in accordance with Behera et al (2018) and Saurabh Kumar (2010), who also reported corneal opacity, high temperature and lymphnode enlargement.…”
Section: Resultssupporting
confidence: 89%
“…In dogs, the prevalence of T. evansi was observed higher in Mongrel than that of other recognized breeds. The young ones below 2 years of age are more commonly affected (Prasad et al, 2015). Absence of the disease transmitting vector is the major reason for non-prevalence of other trypanosome species.…”
Section: Trypanosomiasismentioning
confidence: 99%
“…However both species seem to produce intravascular and extravascular lesions in their hosts (Losos and Ikede 1972;Biswas et al 2001Biswas et al , 2010Rodrigues et al 2009;Bal et al 2012). Prasad et al (2013) studied the prevalece of trypanosomiasis in certain areas of Andhra Pradesh.…”
Section: Introductionmentioning
confidence: 99%